ISSUES AND SOLUTIONS WHILE TEACHING ENGLISH GRAMMAR (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Teaching English grammar is one of the most important aspects of foreign language education in Uzbekistan. Despite the growing interest in English due to globalization and international collaboration, many teachers and students face difficulties in understanding and applying grammar rules effectively. This article discusses the main issues observed in the Uzbek educational context and offers practical solutions based on pedagogical research, local experiences, and modern teaching approaches.